1996
DOI: 10.1029/96jb02295
|View full text |Cite
|
Sign up to set email alerts
|

S wave attenuation and site effects in the region of Friuli, Italy

Abstract: We used strong motion records from the 1976 Friuli earthquake (M 6.4) and 10 of the biggest aftershocks recorded by the National Accelerograph Network of the Electrical Power Company of Italy to estimate the quality factor Q of S waves in this region. The wide distance range of the recordings (10 < r < 190 km) permits us to analyze the spectral amplitude decay of the records using a nonparametric approach [e.g., Anderson and Quaas, 1988; Castro et al., 1990; Anderson, 1991]. We obtained attenuation functions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…As stated in many studies (Mayeda et al 2003;Mayeda et al 1996) the stability of coda measurements with respect to the S amplitudes suggests that results from coda analysis may be more reliable. Moreover, they are consistent with Castro et al 1996 andConsole andRovelli, 1981 who observed low values of Q for this region.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…As stated in many studies (Mayeda et al 2003;Mayeda et al 1996) the stability of coda measurements with respect to the S amplitudes suggests that results from coda analysis may be more reliable. Moreover, they are consistent with Castro et al 1996 andConsole andRovelli, 1981 who observed low values of Q for this region.…”
Section: Resultssupporting
confidence: 79%
“…Within Northern Italy, the Q parameter has been defined using one-dimensional models for different sub-regions (e.g., Morasca et al 2006 and, for the Western Alps; Thouvenot, 1983, Castro et al 2008 for the Central Alps; Malagnini et al 2002, Castro et al 1996and Console and Rovelli, 1981 for the Eastern Alps). The motivation for improving upon the 2-D attenuation model for Northern Italy is several fold.…”
Section: Introductionmentioning
confidence: 99%
“…This evaluated apparent Q factor with low Q 0 and value of N near to 1 indicates high attenuation characteristics in this region and is similar to the results have been found for other tectonically active regions of Iran and the world [Rovelli 1982, Hellweg et al 1995, Yoshimoto et al 1993, Castro et al 1996, Bindi et al 2006, Motazedian 2006 amongst others].…”
supporting
confidence: 87%
“…Castro et al 1990Castro et al , 1996Dutta et al 2003;Oth et al 2011]. Here we provide a brief description of the GIT method and refer the reader to the above-mentioned papers for more in-depth details of this technique.…”
Section: Generalized Inversion Techniquementioning
confidence: 99%
“…We therefore assume S i ( f ) is also independent of frequency. The geometrical spreading (Castro et al, 1996), G(R), is considered to be proportional to (1/R) k , where k is the geometrical spreading coefficient, which chiefly depends on wave type. k = 1.0 implies spherical spreading of body waves and k = 0.5 represents cylindrical spreading of surface waves.…”
Section: Methodsmentioning
confidence: 99%